Students’ performance in microeconomics: Evidence from vavuniya campus, Sri lanka - Thayaparan, A.; Gunathilaka, G.Y.N. (University of Jaffna, 2020)
This study examined the factors affecting the performance of undergraduate students in microeconomics at Vavuniya campus, Sri Lanka. For this purpose, a survey is conducted to collect the data using a sample of 85 students, who enrolled in microeconomics during their first year first semester in the academic year 2015/2016. The data on students’ performance in microeconomics measured in terms of their grades they obtained for the subject, demographic characters with family background and educational factors gathered from the questionnaire. The collected data was analysed using frequency, chi- square test, ordered probit regression and marginal effects in the study. Frequency of the students’ grades revealed that, nearly 59% of them got grade B while 9.4% of them received grade A and 4.7% of the students received grade D. Chi - square test found that family stress and frequency of the study habits significantly associates with the students’ grades in the subject while the grade obtained in general English in G.C.E (A/L) and the usage of library facilities were less associated in the study. Results of ordinal probit model suggested that among the variables related to demographic characteristics with family background, gender and family stress are the good predictors of student performance in microeconomics whereas among educational factors allocation of time, economics as a subject taken by the students in G.C.E (A/L), mathematics knowledge and the usage of library facilities are the other best predictors in students’ performance in the subject.
Keywords: Demographic characteristics; Educational factors; Ordered probit model; Students’ performance